Holistic Education, Holistic Development, Holistic Person - Altan, Mustafa Zülküf; Yıldırım, Taner (Ahmet DURMAZ, 2022)
The development of the individual is much more than the processing, development and therefore the appreciation of the academic side of the individual, that is, only the left side of the brain. Subjects such as reading, writing, and math are essential, but they are not the only things an individual must learn as s/he grows up, which will help them succeed in life and become both a good person and a good citizen. The philosophy of “holistic teaching, development, holistic person”, which we have been hearing often in recent years but is never a new philosophy, has become a popular and effective way of educating children. So, what is meant by “holistic teaching, development and person” and what does it mean? In this article, this question will be tried to be answered and suggestions will be made to both parents and teachers.

Bireyin gelişimi, bireyin akademik yönünün yani beynin sadece sol tarafının işlenmesinden, geliştirilmesinden ve dolayısıyla takdir görmesinden çok daha fazlasıdır. Okuma, yazma ve matematik gibi konular çok önemlidir, ancak bireyin büyüdükçe öğrenmesi gereken, hayatta başarılı olmasına ve hem iyi bir insan hem de iyi bir vatandaş olmasına yardım edecek tek şey bunlar değildir. Son yıllarda sıklıkla duymaya başladığımız ancak asla yeni olmayan “bütüncül öğretim, bütüncül gelişim, bütüncül insan” felsefesi, çocukları eğitmenin popüler ve etkili bir yolu haline geldi. Peki, bütüncül öğretim, gelişim ve insandan ne kast ediliyor ve ne anlama geliyor? Bu makalede bu soruya cevap verilmeye çalışılacak ve hem ebeveynlere hem de öğretmenlere önerilerde bulunulacaktır.
BÜTÜNCÜL EĞİTİM, BÜTÜNCÜL GELİŞİM, BÜTÜNCÜL İNSAN
Keywords: Other Fields of Education; Alan Eğitimleri